PENGARUH PENERAPAN MODEL PEMBELAJARAN PENGAJUAN DAN PEMECAHAN MASALAH (JUCAMA) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DITINJAU DARI SELF REGULATED LEARNING - Endang Fadillah; Irma Fitri (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to determine the effect of the Problem-posing and Problem-solving (JUCAMA) learning model on students’ mathematical creative thinking skills as viewed from the perspective of self-regulated learning. The study employed an experimental method with a factorial experimental design. The research sample was selected using cluster random sampling. Data were collected through a mathematical creative thinking test, a self-regulated learning questionnaire, and an observation sheet, and were then analyzed using a two-way ANOVA. The results indicate that students who learned using the JUCAMA model demonstrated superior mathematical creative thinking abilities compared to those who learned through conventional instruction. Furthermore, no significant differences in mathematical creative thinking abilities were found based on levels of self-regulated learning, and no interaction was observed between the instructional model and self-regulated learning regarding students’ mathematical creative thinking abilities.